Perception of female nurse towards its male nurse co-worker - Dhami, Kabita; Shah, Nisha Kumari; Shah, Pammi; K.C., Nyamika; Pokhrel, Khushi; K.C, Mamta (Journal of Nepal Health Research Council, 2024)
Background: Caring is a universally accepted concept attributed to the nursing profession despite its many nebulous and elusive interpretations. Nursing is seen primarily as a feminine occupation, people get surprised when they see and hear about a male nurse. It is one of the few professions where women outnumber men greatly as it deals with care and nurture. This study aims to assess the female nurse attitude at male nurses in Nepal. Methods: A cross-sectional study was conducted in Biratnagar, Morang from the month of March to May 2023. Ethical clearance was obtained from IRC of Nobel Medical College Teaching Hospital, Biratnagar. Web-based computerized data were collected among 200 female nurses using whats app and Messenger. Data were collected using the Likert scale (AMnQ), which is a standardized 5-point Likert scale that assesses female nurses’ attitudes toward male nurses. SPSS V 23 was used to analyze the data using descriptive and inferential statistical techniques. Results: In this study, more than half (55.0%) of the nurses have low-level attitudes toward male nurses. Furthermore, nearly half (48.5%) disagree nursing is suitable only for females, More than one-third (36.5%) disagree nursing is considered a low-level occupation for males, half of them (50%) strongly disagree male and female nurses both are equally required in the nursing profession and (35%) agrees people do not prefer to send males for the nursing profession. Conclusions: Thus the study concludes that majority of the female nurses have low attitude towards male nurses. Therefore, it can be considered as an initiation for having a conversation regarding making gender equality in nursing and creating awareness about the roles and their importance in this profession. Keywords Attitude; female nurse; male nurse.